1990
DOI: 10.1111/j.1432-1033.1990.tb19126.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of the cysG gene of Escherichia coli K‐12 during aerobic and anaerobic growth

Abstract: The 74-min region of the Escherichiu coli chromosome includes five open reading frames of known sequence. The first and last of these genes, nirB and cysG, are transcribed in the same direction and both are essential for NADH-dependent nitrite reductase activity. The functions of the other genes, nirD, nirE and nirC, which are located between nirB and cysG, are unknown. The nirB gene is transcribed from a promoter which is anaerobically induced, expression being dependent on the transcription activator protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
4
18
1
Order By: Relevance
“…Previous work on E. coli and S. typhimurium has suggested that the cysG gene is in an operon with and downstream of the structural gene for nitrite reductase, nirB (31,32,41). Our data agree with that conclusion.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous work on E. coli and S. typhimurium has suggested that the cysG gene is in an operon with and downstream of the structural gene for nitrite reductase, nirB (31,32,41). Our data agree with that conclusion.…”
Section: Resultssupporting
confidence: 92%
“…Transcription of the cysG gene was induced in response to nitrite when cells were grown under anaerobic conditions. Molecular analysis of the cysG gene in E. coli suggests that the gene is in an operon with the nirB gene, which encodes the structural gene for the NADH-dependent nitrite reductase (25,31,32). Sequence analysis of the cysG gene suggests that this is also the case in S. typhimurium (41).…”
mentioning
confidence: 99%
“…1. Although the function, if any, of the central three open reading frames is unknown, we shall show in the following paper [18] that transcripts starting at nirB cross nirD,E,C into cysG. They have therefore been designated nirD, nirE and nirC.…”
Section: Resultsmentioning
confidence: 92%
“…2). Although nirC is transcribed under the control of the nirB promoter [18], far less NirC than NirB protein accumulates in the bacteria (unpublished results). Decreased expression of nirC relative to nirB could be due to transcription termination between the two genes, to a weaker ribosome binding site preceding nirC, or to the unfavorable pattern ofcodon usage in the N-terminal region of the protein.…”
Section: N N D Q K a I T E T T E Q L I N E P L D R R G E V V L V G A mentioning
confidence: 89%
“…Transcription of the cysJIH region of the operon is enhanced in response to N-acetyl-L-serine, the cysteine precursor, by the LysR-like transcription factor CysB (60). Despite its name, siroheme synthase (CysG) is part of the nitrate regulon, expressed constitutively at low levels but not overexpressed in response to sulfite starvation (61,62). Transcription of the nirBDCG-cysG region of the operon is enhanced in response to NarL and NarP, which sense nitrite/ nitrate, or the Fnr transcription factor, which senses oxygen (63).…”
Section: Apo-sirhp Is a Tetramer-thementioning
confidence: 99%